#BlackLivesMatter: An Analysis of the Movement as Social Drama. Issue 1 (February 2020) - Jones, Leslie Kay
Scholars agree that the United States is experiencing a new black civil and human rights movement called #BlackLivesMatter and that the Internet is pivotal to that movement. Protests in Ferguson, Missouri, and in Baltimore, Maryland, dominated national attention for months through 2014 and 2015. Protesters have successfully gained the attention of elite power brokers, a necessary step in the social movement process. #BlackLivesMatter has many insights to provide about mobilization, if researchers take black American discursive power and intellectual production more seriously as subjects of analysis. This article argues that a dramaturgy framework reveals important meaning making that occurs on the periphery of a social movement. In this periphery, my analysis shows that black social media publics are harbingers of racial progress. Introducing the concept of a Greek Chorus to the dramaturgy framework better clarifies the role that Twitter plays in the movement as a public space where outside observers negotiate their own meaning making surrounding the movement's claims and strategies. Conceptualizing movement mechanics in this way provides a clearer understanding of the importance of digital media in the contemporary black civil rights movement without relying on technological determinism, reducing social media to a structural component of the movement, or undermining the importance of physicality to protest.